Activated carbon and preparation method thereof, capacitor

The mesoporous pore volume of activated carbon is regulated through the low-temperature granulation-activated process, ensuring that the pore size is distributed in the range of 1-3 nm, which solves the problem of structure collapse of activated carbon during circulation, and achieves high capacity and long cycles Taking into account life and reducing production costs.

CN118645373BActive Publication Date: 2024-12-24SHENZHEN BTR NEW ENERGY TECH RES INST CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411111110.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-14
Publication Date
2024-12-24
Estimated Expiration
2044-08-14

AI Technical Summary

Technical Problem

The structure collapse of existing activated carbon during circulation causes capacity attenuation, making it difficult to take into account high capacity and long cycle life, and the preparation process cost is high.

Method used

Using low-temperature granulation-activation process, the mesoporous pore volume of activated carbon is regulated through CO2-assisted granulation and secondary activation of water vapor, ensuring that the pore size is distributed within the range of 1-3 nm, and there are three characteristic pore volume peaks to achieve stable electrochemical cycles. performance.

Benefits of technology

It improves the electrochemical cycle stability and capacity of activated carbon, while reducing production costs, achieving both high capacity and long cycle life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118645373B_ABST
    Figure CN118645373B_ABST
Patent Text Reader

Abstract

The present application provides an activated carbon and a preparation method and a capacitor, and relates to the field of energy technology. The activated carbon has a progressive pore structure, and the electrolyte ions first enter the mesopores through the surface gaps of the activated carbon material, the gaps between the powders, etc. The mesoporous pore structure provides a sufficiently stable ion migration channel, and the ions can enter the first micropores relatively easily through the mesopores. This structure will ensure that the electrolyte ions can be easily adsorbed and fill the first micropores, which ensures that the carbon material has a sufficiently high large current charge and discharge performance. After the first micropores are filled, the electrolyte ions can more advantageously diffuse to the second micropores, and the second micropores have appropriate ion adsorption space. The surface of the second micropore structure can well adsorb a layer of electrolyte ions. The activated carbon product can maintain a high mass specific capacitance while having stable electrochemical cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of energy technology, and in particular to an activated carbon and a preparation method thereof, and a capacitor. Background Art

[0002] my country's supercapacitor market is growing rapidly, with many application scenarios, such as trams, energy-saving elevators, wind power equipment, etc. Activated carbon is the core material electrode of supercapacitors, and its demand is also increasing. In the existing technology, activated carbon is mainly prepared by activation, and the activation process is mainly divided into physical activation and chemical activation.

[0003] The characteristics of alkaline activated carbon products are high micropore ratio, high specific surface area, and rich microscopic pore structure, which provides a large number of ion adsorption sites. This type of activated carbon product has high mass specific capacitance. However, the micropores in the activated carbon will partially collapse during the cycle, reducing the ion adsorption space and reducing the rich micropore ratio in the pore structure, which will lead to rapid decay of the supercapacitor cycle capacity.

[0004] At present, the traditional alkali activation process still has difficulty in stably and accurately preparing high-capacity and high-cycle-life activated carbon by adjusting the activation process parameters, alkali mixing methods and alkali mixing process parameters. This may be because it is difficult to control the uniformity of the reaction in large-scale production, and it is easy to over-react during high-temperature activation, resulting in excessive mesoporous content. The alkali metal elements in the auxiliary materials will also penetrate into the pores during the high-temperature reaction, resulting in complicated subsequent processing and high costs. Summary of the invention

[0005] The purpose of the present application is to provide an activated carbon and a preparation method thereof, and a capacitor, aiming to solve the problem that the existing activated carbon has high cost and is difficult to balance capacity and cycle life.

[0006] To achieve the above objectives, the present application provides an activated carbon, wherein the activated carbon has three characteristic pore volume peaks in the pore size distribution of 1-3 nm: peak A, peak B, and peak C;

[0007] The pore diameter of the A peak is 1 nm-1.2 nm, and the pore volume peak is 0.02-0.05 cc / g; preferably, the pore volume peak of the A peak is 0.03-0.05 cc / g;

[0008] The pore diameter of the B peak is 1.5 nm-1.7 nm, and the pore volume peak is 0.008-0.03 cc / g; preferably, the pore volume peak of the B peak is 0.02-0.03 cc / g;

[0009] The pore diameter at the C peak is 1.9 nm-2.3 nm, and the pore volume peak is 0.001-0.01 cc / g; preferably, the pore volume peak at the C peak is 0.005-0.01 cc / g.

[0010] In some embodiments, the mesopore volume of the activated carbon is 0.01-0.10 cc / g. Preferably, the mesopore volume of the activated carbon is 0.05-0.09 cc / g.

[0011] In some embodiments, the specific surface area of ​​the activated carbon is 1400-2000 m 2 / g.

[0012] In some embodiments, at least one of the following conditions is met:

[0013] (1) The total pore volume of the activated carbon is 0.6-0.9 cc / g;

[0014] (2) The proportion of micropore volume of the activated carbon to the total pore volume is 85%-95%;

[0015] (3) The activated carbon has a tap density of 0.28-0.40 g / cc;

[0016] (4) The activated carbon has a compacted density of 0.45-0.6 g / cc;

[0017] (5) The moisture content of the activated carbon is less than 3%;

[0018] (6) The powder conductivity of the activated carbon is 10 - 40 S / cm;

[0019] (7) The median particle size of the activated carbon is 3-8 um.

[0020] The present application also provides a method for preparing the above-mentioned activated carbon, comprising:

[0021] mixing the carbonized material with the activator to obtain a mixed material;

[0022] The mixed material is first activated in an inert gas and CO2 gas to obtain a granulated material;

[0023] The granulated material is subjected to a second activation in water vapor to obtain an activated material;

[0024] The activated material is purified, crushed and sintered to obtain the activated carbon.

[0025] In some embodiments, at least one of the following conditions is met:

[0026] A. The carbonized material includes at least one of petroleum coke, coal, coconut shell, apricot shell, walnut shell, bamboo, phenolic resin, urea-formaldehyde resin, polyvinyl chloride, and asphalt;

[0027] B. the activator is at least one of sodium hydroxide, potassium hydroxide and calcium hydroxide;

[0028] C. The mixing method is mechanical mixing;

[0029] D. The mass ratio of the carbonized material to the activator is 1:(1.2-2.5).

[0030] In some embodiments, at least one of the following conditions is met:

[0031] E. The flow rate of the inert gas is 200-1000 sccm;

[0032] F. The flow rate of the CO2 gas is 5-200 sccm;

[0033] G. the temperature of the first activation is 350-650°C;

[0034] H. The first activation holding time is 10-60 min.

[0035] In some embodiments, at least one of the following conditions is met:

[0036] a. The flow rate of the water vapor is 0.1 L / min-0.3 L / min;

[0037] b. The second activation temperature is 550-800°C; preferably, the second activation temperature is 700-800°C;

[0038] c. The second activation holding time is 1-3h.

[0039] In some embodiments, the purification includes water washing and acid washing; and the preparation method satisfies at least one of the following conditions:

[0040] d. The mass ratio of the water to the carbonized material is 1-100:1;

[0041] e. The mass concentration of the acid is 10-30%;

[0042] f. The acid comprises at least one of sulfuric acid, hydrochloric acid, hydrofluoric acid and nitric acid.

[0043] The present application also provides a capacitor using the above-mentioned activated carbon as an electrode.

[0044] Compared with the prior art, the beneficial effects of this application include:

[0045] The activated carbon provided in this application controls the appropriate pore size range, and there are three characteristic pore volume peaks in the 1-3 nm pore size distribution: A peak, B peak, and C peak, which can keep the activated carbon product at a high mass specific capacitance while having stable electrochemical cycle performance. In supercapacitor devices, electrolyte ions first enter the mesopores through the surface gaps of the activated carbon material, the gaps between the powders, etc. The mesopore (C peak) pore structure provides a sufficiently stable ion migration channel, and the ions can enter the first micropore (B peak) relatively easily through the mesopore (C peak). This structure will ensure that the electrolyte ions can easily adsorb and fill the first micropores, which ensures that the carbon material has a sufficiently high high current charge and discharge performance. When the first micropore is filled, the electrolyte ions can more advantageously diffuse to the second micropore (A peak), the second micropore has an appropriate ion adsorption space (electrolyte ion diameter ~ 0.68 nm), and the surface of the second micropore structure can well adsorb a layer of electrolyte ions. This layer-by-layer progressive pore size structure can ensure that sufficient electrolyte ions can diffuse smoothly and be adsorbed in the activated carbon pore structure. At the same time, the appropriate mesopores and first micropores ensure the electrochemical cycle stability of the material.

[0046] The preparation method of activated carbon provided in the present application adopts a low-temperature granulation-activation process, which can realize continuous operation and improve production capacity. The method mainly adopts a composite activation process to realize the mesoporous pore volume regulation of activated carbon, promotes the expansion of the mesoporous pore volume of activated carbon by CO2-assisted granulation and secondary activation by water vapor, realizes the improvement of high-temperature cycle stability of activated carbon, and takes into account the mass specific capacitance and cycle stability of activated carbon products. The main feature of this method is the low-temperature activation process, which avoids the deep embedding of alkali metal ions in the pores of activated carbon caused by high activation temperature, and greatly reduces the processing cost of the purification process. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0048] Figure 1 is an optical schematic diagram of the granulated material of Example 1;

[0049] Figure 2 This is an optical schematic diagram of the activated material of Example 1;

[0050] Figure 3 Schematic diagram of pore size distribution of activated carbon in Example 2;

[0051] Figure 4 Schematic diagram of pore size distribution of activated carbon in Example 4;

[0052] Figure 5 Schematic diagram of pore size distribution of activated carbon in Example 7;

[0053] Figure 6 Schematic diagram of pore size distribution of activated carbon in Example 8;

[0054] Figure 7 Schematic diagram of pore size distribution of activated carbon in Comparative Example 1;

[0055] Figure 8 Schematic diagram of the pore size distribution of the activated carbon of Comparative Example 2. DETAILED DESCRIPTION

[0056] As used herein:

[0057] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0058] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0059] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0060] In these examples, parts and percentages are by mass unless otherwise indicated.

[0061] "Mass parts" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass parts of component A are a parts and the mass parts of component B are b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass parts of all components is not limited to 100 parts.

[0062] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0063] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0064] Example 1

[0065] Example 1 provides a method for preparing low-cost and high-capacity activated carbon, comprising the following steps:

[0066] Coconut shell carbonized material was prepared according to the existing carbonization process. 10 kg of coconut shell carbonized material and 20 kg of potassium hydroxide were weighed and placed in a VC mixer for stirring and mixing for 15 min to obtain a mixture.

[0067] The mixed material obtained above was placed in a rotary kiln, the nitrogen flow rate was controlled at 400 sccm, the temperature was raised to 420 °C at a rate of 1.5 °C / min, and CO2 gas was introduced, the gas flow rate was controlled at 50 sccm, and the holding time was 30 min to obtain a granulated material, the optical schematic diagram of which is shown in FIG. Figure 1 As shown, the feasibility of the rotary kiln granulation process is demonstrated.

[0068] Then the temperature was raised to 600℃ at a rate of 1.5℃ / min, and water vapor was introduced at a rate of 0.2L / min. The temperature was kept for 1 hour. After the activation reaction was completed, the activated material was poured out for purification. The optical schematic diagram of the activated material is shown in Figure 2 As shown, it indicates that the particles can still remain unchanged after being activated by steam in the rotary kiln.

[0069] The activated material is placed in a purification reactor for washing. The mass of pure water for each washing is 100 kg, that is, the water-to-material ratio is 10:1. Wash 5 times and test the liquid pH value <10. Prepare a sulfuric acid / hydrochloric acid mixed solution with a mass concentration of 15%, in which the ratio of sulfuric acid: hydrochloric acid is 2:1, soak for about 2 hours, wash a certain number of times, and when the pH value of the washing liquid is >6.5, discharge the material and centrifuge and dry to obtain the purified material. The purified material obtained can be subjected to a series of crushing and sintering treatments to obtain the finished activated carbon.

[0070] Example 2

[0071] Example 2 provides a method for preparing low-cost and high-capacity activated carbon, comprising the following steps:

[0072] Coconut shell carbonized material was prepared according to the existing carbonization process. 10 kg of coconut shell carbonized material and 20 kg of potassium hydroxide were weighed and placed in a VC mixer for stirring and mixing for 15 min to obtain a mixture.

[0073] The mixed material obtained above was placed in a rotary kiln, the nitrogen flow rate was controlled at 400 sccm, the temperature was raised to 520 °C at a heating rate of 1.5 °C / min, and CO2 gas was started to be introduced, the gas flow rate was controlled at 50 sccm, and the insulation time was 30 minutes to obtain granulated material.

[0074] Then the temperature was raised to 600 °C at a rate of 1.5 °C / min, and water vapor was introduced at a rate of 0.2 L / min. The temperature was kept constant for 1 h. After the activation reaction was completed, the activated material was poured out for purification.

[0075] The activated material obtained is placed in a purification reactor for washing. The amount of water for each washing is 100 kg, that is, the water-to-material ratio is 10:1. Wash 5 times and test the liquid pH value <10. Prepare a sulfuric acid / hydrochloric acid mixed solution with a mass concentration of 15%, in which the ratio of sulfuric acid: hydrochloric acid is 2:1, and soak for about 2 hours. After washing a certain number of times, when the pH value of the washing liquid is >6.5, discharge the material and centrifuge and dry it to obtain the purified material. The purified material obtained can be subjected to a series of crushing and sintering treatments to obtain the finished activated carbon, and its pore size distribution diagram is shown as follows Figure 3 shown.

[0076] according to Figure 3 It can be seen that the pore size distribution of the activated carbon in Example 2 shows three main characteristic peaks, and the peak range is fixed, peak A is at 1.19 nm, and the peak is at 0.023 cc / g; peak B is at 1.68 nm, and the peak is at 0.009 cc / g; peak C is at 2.1 nm, and the peak is at 0.0019 cc / g, indicating that the activated carbon obtained by the alkali + water vapor mixed activation process has significant characteristic peaks.

[0077] Example 3

[0078] Example 3 provides a method for preparing low-cost and high-capacity activated carbon, comprising the following steps:

[0079] Coconut shell carbonized material was prepared according to the existing carbonization process. 10 kg of coconut shell carbonized material and 20 kg of potassium hydroxide were weighed and placed in a VC mixer for stirring and mixing for 15 min to obtain a mixture.

[0080] The mixed material obtained above was placed in a rotary kiln, the nitrogen flow rate was controlled at 400 sccm, the temperature was raised to 620 °C at a heating rate of 1.5 °C / min, and CO2 gas was started to be introduced, the gas flow rate was controlled at 50 sccm, and the insulation time was 30 minutes to obtain granulated material.

[0081] Then, the temperature was further lowered to 600 °C at a rate of 1.5 °C / min, and water vapor was introduced at a rate of 0.2 L / min. The temperature was kept for 1 h. After the activation reaction was completed, the activated material was poured out for purification.

[0082] The activated material is placed in a purification reactor for washing. The amount of water for each washing is 100 kg, that is, the water-to-material ratio is 10:1. Wash 5 times and test the liquid pH value <10. Prepare a sulfuric acid / hydrochloric acid mixed solution with a mass concentration of 15%, in which the ratio of sulfuric acid: hydrochloric acid is 2:1, soak for about 2 hours, wash a certain number of times, and when the pH value of the washing liquid is >6.5, discharge the material and centrifuge and dry to obtain the purified material. The purified material is subjected to a series of crushing and sintering treatments to obtain the finished activated carbon.

[0083] Example 4

[0084] Example 4 provides a method for preparing low-cost and high-capacity activated carbon, comprising the following steps:

[0085] Coconut shell carbonized material was prepared according to the existing carbonization process. 10 kg of coconut shell carbonized material and 20 kg of sodium hydroxide were weighed and placed in a VC mixer for stirring and mixing for 15 min to obtain a mixture.

[0086] The mixed material obtained above was placed in a rotary kiln, the nitrogen flow rate was controlled at 400 sccm, the temperature was raised to 520 °C at a heating rate of 1.5 °C / min, and CO2 gas was started to be introduced, the gas flow rate was controlled at 50 sccm, and the insulation time was 30 minutes to obtain granulated material.

[0087] Then the temperature was raised to 800 °C at a rate of 1.5 °C / min, and water vapor was introduced at a rate of 0.2 L / min. The temperature was kept constant for 1 h. After the activation reaction was completed, the activated material was poured out for purification.

[0088] The activated material obtained is placed in a purification reactor for washing. The amount of water for each washing is 100 kg, that is, the water-to-material ratio is 10:1. Wash 5 times and test the liquid pH value <10. Prepare a sulfuric acid / hydrochloric acid mixed solution with a mass concentration of 15%, in which the ratio of sulfuric acid: hydrochloric acid is 2:1, and soak for about 2 hours. After washing a certain number of times, when the pH value of the washing liquid is >6.5, discharge the material and centrifuge and dry it to obtain the purified material. The purified material obtained can be subjected to a series of crushing and sintering treatments to obtain the finished activated carbon, and its pore size distribution diagram is shown as follows Figure 4 The measured powder data showed that the proportion of micropore volume to total pore volume was 93.05%, the tap density was 0.31 g / cc, the compacted density was 0.46 g / cc, the moisture content was 0.2%, the powder conductivity was 13 S / cm, and the median particle size was 6.5 um.

[0089] according to Figure 4 It can be seen that the pore size distribution of the activated carbon in Example 4 shows three main characteristic peaks, and the peak range is fixed, the A peak is at 1.14 nm, and the peak is at 0.039 cc / g; the B peak is at 1.68 nm, and the peak is at 0.022 cc / g; the C peak is at 2.20 nm, and the peak is at 0.006 cc / g, indicating that the activated carbon obtained by the alkali + water vapor mixed activation process has significant characteristic peaks.

[0090] Example 5

[0091] Example 5 provides a method for preparing low-cost and high-capacity activated carbon, comprising the following steps:

[0092] Coconut shell carbonized material was prepared according to the existing carbonization process. 10 kg of coconut shell carbonized material and 20 kg of sodium hydroxide were weighed and placed in a VC mixer for stirring and mixing for 15 min to obtain a mixture.

[0093] The mixed material obtained above was placed in a rotary kiln, the nitrogen flow rate was controlled at 400 sccm, the temperature was raised to 620 °C at a heating rate of 1.5 °C / min, and CO2 gas was started to be introduced, the gas flow rate was controlled at 50 sccm, and the insulation time was 30 minutes to obtain granulated material.

[0094] Then the temperature was raised to 800°C at a rate of 1.5°C / min, and water vapor was introduced at a rate of 0.2 L / min. The temperature was kept constant for 1 h. After the activation reaction was completed, the activated material was poured out for purification.

[0095] The activated material is placed in a purification reactor for washing. The amount of water for each washing is 100 kg, that is, the water-to-material ratio is 10:1. Wash 5 times and test the liquid pH value <10. Prepare a sulfuric acid / hydrochloric acid mixed solution with a mass concentration of 15%, in which the ratio of sulfuric acid: hydrochloric acid is 2:1, soak for about 2 hours, wash a certain number of times, and when the pH value of the washing liquid is >6.5, discharge the material and centrifuge and dry to obtain the purified material. The purified material is subjected to a series of crushing and sintering treatments to obtain the finished activated carbon.

[0096] Example 6

[0097] Example 6 provides a method for preparing low-cost and high-capacity activated carbon, comprising the following steps:

[0098] Coconut shell carbonized material was prepared according to the existing carbonization process. 10 kg of coconut shell carbonized material and 20 kg of potassium hydroxide were weighed and placed in a VC mixer for stirring and mixing for 15 min to obtain a mixture.

[0099] The mixed material obtained above was placed in a rotary kiln, the nitrogen flow rate was controlled at 400 sccm, the temperature was raised to 420 °C at a heating rate of 1.5 °C / min, and CO2 gas was started to be introduced, the gas flow rate was controlled at 50 sccm, and the insulation time was 30 minutes to obtain granulated material.

[0100] Then the temperature was raised to 700 °C at a rate of 1.5 °C / min, and water vapor was introduced at a rate of 0.2 L / min. The temperature was kept constant for 1 h. After the activation reaction was completed, the activated material was poured out for purification.

[0101] The activated material is placed in a purification reactor for washing. The amount of water for each washing is 100 kg, that is, the water-to-material ratio is 10:1. Wash 5 times and test the liquid pH value <10. Prepare a sulfuric acid / hydrochloric acid mixed solution with a mass concentration of 15%, in which the ratio of sulfuric acid: hydrochloric acid is 2:1, soak for about 2 hours, wash a certain number of times, and when the pH value of the washing liquid is >6.5, discharge the material and centrifuge and dry to obtain the purified material. The purified material is subjected to a series of crushing and sintering treatments to obtain the finished activated carbon.

[0102] Example 7

[0103] Example 7 provides a method for preparing low-cost and high-capacity activated carbon, comprising the following steps:

[0104] Coconut shell carbonized material was prepared according to the existing carbonization process. 10 kg of coconut shell carbonized material and 20 kg of potassium hydroxide were weighed and placed in a VC mixer for stirring and mixing for 15 min to obtain a mixture.

[0105] The mixed material obtained above was placed in a rotary kiln, the nitrogen flow rate was controlled at 400 sccm, the temperature was raised to 520 °C at a heating rate of 1.5 °C / min, and CO2 gas was started to be introduced, the gas flow rate was controlled at 50 sccm, and the insulation time was 30 minutes to obtain granulated material.

[0106] Then the temperature was raised to 800 °C at a rate of 1.5 °C / min, and water vapor was introduced at a rate of 0.2 L / min. The temperature was kept constant for 1 h. After the activation reaction was completed, the activated material was poured out for purification.

[0107] The activated material obtained is placed in a purification reactor for washing. The amount of water for each washing is 100 kg, that is, the water-to-material ratio is 10:1. Wash 5 times and test the liquid pH value <10. Prepare a sulfuric acid / hydrochloric acid mixed solution with a mass concentration of 15%, in which the ratio of sulfuric acid: hydrochloric acid is 2:1, and soak for about 2 hours. After washing a certain number of times, when the pH value of the washing liquid is >6.5, discharge the material and centrifuge and dry it to obtain the purified material. The purified material obtained can be subjected to a series of crushing and sintering treatments to obtain the finished activated carbon, and its pore size distribution diagram is shown as follows Figure 5 shown.

[0108] according to Figure 5 It can be seen that the pore size distribution of the activated carbon in Example 7 shows three main characteristic peaks, and the peak range is fixed, peak A is at 1.19 nm, with a peak at 0.043 cc / g; peak B is at 1.6 nm, with a peak at 0.024 cc / g; peak C is at 2.0 nm, with a peak at 0.007 cc / g, indicating that the activated carbon obtained by the alkali + water vapor mixed activation process has significant characteristic peaks.

[0109] Example 8

[0110] Example 8 provides a method for preparing low-cost and high-capacity activated carbon, comprising the following steps:

[0111] Coconut shell carbonized material was prepared according to the existing carbonization process. 10 kg of coconut shell carbonized material and 20 kg of sodium hydroxide were weighed and placed in a VC mixer for stirring and mixing for 15 min to obtain a mixture.

[0112] The mixed material obtained above was placed in a rotary kiln, the nitrogen flow rate was controlled at 400 sccm, the temperature was raised to 420 °C at a heating rate of 1.5 °C / min, and CO2 gas was started to be introduced, the gas flow rate was controlled at 50 sccm, and the insulation time was 30 minutes to obtain granulated material.

[0113] Then the temperature was raised to 800 °C at a rate of 1.5 °C / min, and water vapor was introduced at a rate of 0.2 L / min. The temperature was kept constant for 1 h. After the activation reaction was completed, the activated material was poured out for purification.

[0114] The activated material obtained is placed in a purification reactor for washing. The amount of water for each washing is 100 kg, that is, the water-to-material ratio is 10:1. Wash 5 times and test the liquid pH value <10. Prepare a sulfuric acid / hydrochloric acid mixed solution with a mass concentration of 15%, in which the ratio of sulfuric acid: hydrochloric acid is 2:1, and soak for about 2 hours. After washing a certain number of times, when the pH value of the washing liquid is >6.5, discharge the material and centrifuge and dry it to obtain the purified material. The purified material obtained can be subjected to a series of crushing and sintering treatments to obtain the finished activated carbon, and its pore size distribution diagram is shown as follows Figure 6 shown.

[0115] according to Figure 6 It can be seen that the pore size distribution of the activated carbon in Example 8 shows three main characteristic peaks, and the peak range is fixed, the A peak is at 1.2 nm, and the peak is at 0.034 cc / g; the B peak is at 1.65 nm, and the peak is at 0.023 cc / g; the C peak is at 2.2 nm, and the peak is at 0.007 cc / g, indicating that the activated carbon obtained by the alkali + water vapor mixed activation process has significant characteristic peaks.

[0116] Example 9

[0117] Example 9 provides a method for preparing low-cost and high-capacity activated carbon, comprising the following steps:

[0118] Apricot shell carbonized material was prepared according to the existing carbonization process. 10 kg of apricot shell carbonized material and 20 kg of potassium hydroxide were weighed and placed in a VC mixer for stirring and mixing for 15 min to obtain a mixture.

[0119] The mixed material obtained above was placed in a rotary kiln, the nitrogen flow rate was controlled at 400 sccm, the temperature was raised to 420 °C at a heating rate of 1.5 °C / min, and CO2 gas was started to be introduced, the gas flow rate was controlled at 50 sccm, and the insulation time was 30 minutes to obtain granulated material.

[0120] Then the temperature was raised to 800 °C at a rate of 1.5 °C / min, and water vapor was introduced at a rate of 0.2 L / min. The temperature was kept constant for 1 h. After the activation reaction was completed, the activated material was poured out for purification.

[0121] The activated material is placed in a purification reactor for washing. The amount of water for each washing is 100 kg, that is, the water-to-material ratio is 10:1. Wash 5 times and test the liquid pH value <10. Prepare a sulfuric acid / hydrochloric acid mixed solution with a mass concentration of 15%, in which the ratio of sulfuric acid: hydrochloric acid is 2:1, soak for about 2 hours, wash a certain number of times, and when the pH value of the washing liquid is >6.5, discharge the material and centrifuge and dry to obtain the purified material. The purified material is subjected to a series of crushing and sintering treatments to obtain the finished activated carbon.

[0122] Comparative Example 1

[0123] Comparative Example 1 provides a method for preparing activated carbon, introducing CO2 to assist granulation and using sodium hydroxide for activation, comprising the following steps:

[0124] Coconut shell carbonized material was prepared according to the existing carbonization process. 10 kg of coconut shell carbonized material and 20 kg of sodium hydroxide were weighed and placed in a VC mixer for stirring and mixing for 15 min to obtain a mixture.

[0125] The mixed material obtained above was placed in a rotary kiln, the nitrogen flow rate was controlled at 400 sccm, the temperature was raised to 520 °C at a heating rate of 1.5 °C / min, and CO2 gas was started to be introduced, the gas flow rate was controlled at 50 sccm, and the insulation time was 30 min to obtain granulated material.

[0126] Then the temperature was raised to 800 °C at a rate of 1.5 °C / min and kept at that temperature for 1 h. After the activation reaction was completed, the activated material was poured out for purification.

[0127] The activated material obtained is placed in a purification reactor for washing. The amount of water for each washing is 100 kg, that is, the water-to-material ratio is 10:1. Wash 5 times and test the liquid pH value to be <10. Prepare a sulfuric acid / hydrochloric acid mixed solution with a mass concentration of 15%, in which the ratio of sulfuric acid to hydrochloric acid is 2:1, and soak it. After washing a certain number of times, when the pH value of the washing liquid is >6.5, discharge the material and centrifuge and dry it to obtain the purified material. The purified material obtained can be subjected to a series of crushing and sintering treatments to obtain the finished activated carbon. The pore size distribution diagram of the activated carbon in Comparative Example 1 is shown in the figure. Figure 7 As shown. Figure 7 It can be seen that the pore size of the activated carbon in Comparative Example 1 mainly presents two peaks, the left peak is at 1.19 nm, and the peak value is at 0.031 cc / g; the right peak is at 1.63 nm, and the peak value is at 0.013 cc / g.

[0128] Comparative Example 2

[0129] Comparative Example 2 provides a method for preparing activated carbon, which uses only steam activation and includes the following steps:

[0130] Coconut shell carbonized material was prepared according to the existing carbonization process. 10 kg of coconut shell carbonized material was weighed and put into a rotary furnace. The temperature was raised to 800 °C at a heating rate of 1.5 °C / min, and water vapor was introduced at a rate of 0.2 L / min. The temperature was kept warm for 1 h. After the activation reaction was completed, the activated material was poured out for purification.

[0131] The activated material obtained is placed in a purification reactor for washing, equipped with a sulfuric acid / hydrochloric acid mixed solution with a mass concentration of 15%, wherein the ratio of sulfuric acid to hydrochloric acid is 2:1, and the reaction is soaked for 2 hours, followed by pure water washing, with the amount of water for each washing being 100 kg, that is, the water-to-material ratio is 10:1. After washing a certain number of times, when the pH value of the washing liquid is >6.5, the material is discharged and centrifuged and dried to obtain the purified material. The purified material obtained is subjected to a series of pulverization and sintering treatments to obtain the finished activated carbon. The pore size distribution diagram of the activated carbon in Comparative Example 2 is shown in FIG. Figure 8 As shown, the peak position of the pore size distribution is 1.19 nm and the peak value is located at 0.018 cc / g.

[0132] Comparative Example 3

[0133] Comparative Example 3 provides a method for preparing activated carbon, which uses only alkali for activation, comprising the following steps:

[0134] Coconut shell carbonized material was prepared according to the existing carbonization process. 10 kg of coconut shell carbonized material and 20 kg of sodium hydroxide were weighed and placed in a VC mixer for stirring and mixing for 15 min to obtain a mixture.

[0135] The above-obtained mixture was placed in a rotary furnace, the nitrogen flow rate was controlled at 400 sccm, the temperature was raised to 520 °C at a heating rate of 1.5 °C / min, and the temperature was kept for 30 min. Then the temperature was raised to 800 °C at a heating rate of 1.5 °C / min, and N2 was introduced for protection. The flow rate was controlled at 3 L / min and the temperature was kept for 1 h. After the activation reaction was completed, the activated material was poured out for purification.

[0136] The activated material is placed in a purification reactor for washing, equipped with a 15% sulfuric acid / hydrochloric acid mixed solution, where the ratio of sulfuric acid to hydrochloric acid is 2:1, and soaked for 2 hours, followed by pure water washing, each washing water volume is 100 kg, that is, the water-to-material ratio is 10:1, after a certain number of washings, when the pH value of the washing liquid is >6.5, the material is discharged and centrifuged and dried to obtain the purified material. The purified material obtained can be subjected to a series of crushing and sintering treatments to obtain the finished activated carbon.

[0137] Preparation of soft-pack capacitors: The activated carbon materials of Examples 1 to 9 and Comparative Examples 1 to 3 were respectively mixed with LA133 binder and conductive carbon black in a mass ratio of 85:10:5 and evenly coated on an aluminum foil current collector, and vacuum dried at 120°C to obtain electrode sheets, which were then assembled into soft-pack batteries for testing, wherein the separator was Celgard C2400 and the electrolyte was 1 M C8H20BF4N / AN (Xinzhoubang DLC301 electrolyte).

[0138] Performance Test:

[0139] 1.ICP result test

[0140] The trace element test of the purified materials of each embodiment and comparative example was conducted using an Optima 2100DV inductively coupled plasma emission spectrometer.

[0141] 2. The specific surface area and pore volume were obtained by nitrogen adsorption test at 77K using a Microbead tester (model ASAP2460). The specific surface area was calculated using the BET formula (unit: m 2 / g), pore volume V 孔 is the total pore volume of single-point adsorption (in cm³ / g), and the pore size distribution, mesopore volume and other results are calculated using the mathematical model DFT.

[0142] 3. Using GeoPyc1360 Micrometer tap density meter, a certain sample is placed in a measuring cylinder (38 mm diameter), and the container is mechanically vibrated at a high frequency until the test force reaches 180 N. The ratio of the mass of the sample to the volume after tapping is the Micrometer tap density.

[0143] 4. Take 1g of powder and place it in a metal sleeve. Apply 5 tons of pressure. After maintaining this pressure for a certain period of time, the ratio of the sample mass to the compacted volume is the compacted density.

[0144] 5. The moisture content of the powder is tested using a METELOR TOLEDO Karl Fischer coulometric titrator. The test method is based on the direct coulometric titration method in the Karl Fischer method (general method) for moisture content determination of chemical products in GB / T6283-2008.

[0145] 6. Use MCP-DP51 powder conductivity test equipment to test the powder conductivity under 20KN pressure.

[0146] 7. The powder particle size was tested using Malvern MS2000 instrument, based on anhydrous ethanol + water as dispersant, with a refractive index of 2.4 and an occlusion of 5-15%.

[0147] 8. Simple capacity and high temperature cycle performance test

[0148] The capacity and cycle retention rate test methods of the batteries of each embodiment and comparative example are as follows:

[0149] (1) Pre-cycle (10 times): 25 ℃, charging cut-off voltage U, constant current 10 mA / F for charging; then discharge at the lower limit voltage U / 2, constant current 10 mA / F; (2) In a high temperature box at 65 ℃ ~ 70 ℃, charge at a constant current of 10 mA / F to the upper limit voltage U, and keep the constant voltage (U) for a certain time; take out the supercapacitor and cool it to 25 ℃, and then perform charge and discharge tests. The test conditions are the same as the pre-cycle, and the capacity retention rate of the supercapacitor is calculated.

[0150] The ICP test results of the purified materials of various embodiments and comparative examples are shown in Table 1.

[0151] Table 1 Comparison of ICP values ​​of purified materials in various embodiments and comparative examples

[0152]

[0153] Note: ——” indicates that the sample did not require further washing and was not subjected to ICP testing.

[0154] According to Table 1, by comparing Example 1, Example 2 and Example 3, it can be found that the granulation temperature has little effect on the subsequent purification process of the activated carbon, and a lower impurity content can be achieved; since the alkalinity of NaOH is weaker than that of KOH, Examples 4 and 5 use 800°C as the deep activation temperature. Compared with Examples 1 to 3, it can be found that using NaOH as an activating agent will increase the difficulty of subsequent purification; by comparing Example 1, Example 6 and Example 7, it can be found that the deep activation temperature has a greater impact on the subsequent purification process of the activated carbon, especially on the residual content of the K element; by comparing Example 7 with Examples 4 and 5, it can be found that using NaOH as an activating agent and high-temperature activation conditions will increase the difficulty of the purification process, and the residual metal element content in the sample will be higher.

[0155] The specific surface area, pore volume and mesopore volume parameters of the activated carbon of each embodiment and comparative example are shown in Table 2.

[0156] Table 2 Physical parameters of activated carbon in various embodiments and comparative examples

[0157]

[0158] According to Table 2, Examples 1 to 3 show that different granulation temperatures can meet the granulation requirements of activated carbon materials, and can prepare samples with higher specific surface area and mesopore volume; Examples 4 and 5 show that the high-temperature granulation-activation process is also suitable for other activators; Comparison between Examples 1, 2 and 6, 7 shows that a higher deep activation temperature can make the sample produce a higher specific surface area and mesopore volume; Example 9 shows that the invention is also suitable for other carbonized material precursors; Comparison between Example 4 and Comparative Example 1 shows that the alkali activation method will produce a higher specific surface area, and the introduction of water vapor helps to further expand the mesopore volume.

[0159] In the present application, during the granulation process, CO2 and alkali react on the surface of the pellets to form a carbonate layer, which exists in the pores on the surface of the material and further reacts after the subsequent introduction of water vapor to form CO2 gas and alkali. The CO2 gas overflows and creates larger pores on the surface, while the alkali further reacts with the surface of the carbon material to widen the surface pores, which, on the one hand, provides a channel for the gas to overflow from the pores inside the material, and, on the other hand, is more conducive to water vapor entering the pores inside the material for deep activation reaction. The beneficial effect brought about by this is that alkali, CO2, and water vapor are activated together to achieve the expansion of the mesoporous pore volume at low temperature.

[0160] The capacity and high temperature cycle retention rate of the batteries of various embodiments and comparative examples are shown in Table 3.

[0161] Table 3 Simple capacity and high temperature cycle retention rate of batteries in various embodiments and comparative examples

[0162]

[0163] By comparison, it can be found that Example 4, Example 5, Example 6, Example 7, Example 8, Example 9 and Comparative Example 2 can all achieve a high temperature retention rate of more than 80% at 2000 h. This is due to the catalytic effect of water vapor on the activated material, which further increases the proportion of mesopore volume in the total pore volume. This higher mesopore volume helps to improve the stability of the pores during the electrochemical cycle.

[0164] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

[0165] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.

Claims

1. An activated carbon, characterized in that The activated carbon has three characteristic pore volume peaks in the pore size distribution of 1-3 nm: peak A, peak B, and peak C; The pore diameter of peak A is between 1 nm and 1.2 nm, and the pore volume peak is between 0.02 and 0.05 cc / g; The pore diameter of peak B is between 1.5 nm and 1.7 nm, and the pore volume peak is between 0.008 and 0.03 cc / g; The pore diameter of the C peak is 2.0 nm-2.3 nm, and the pore volume peak is 0.005-0.01 cc / g; The mesopore volume of the activated carbon is 0.05-0.09 cc / g.

2. The activated carbon according to claim 1, characterized in that The specific surface area of ​​the activated carbon is 1400-2200m 2 / g.

3. The activated carbon according to claim 2, characterized in that At least one of the following conditions is met: (1) The total pore volume of the activated carbon is 0.6-0.9 cc / g; (2) The proportion of micropore volume of the activated carbon to the total pore volume is 85%-95%; (3) The activated carbon has a tap density of 0.28-0.40 g / cc; (4) The activated carbon has a compacted density of 0.45-0.6 g / cc; (5) The moisture content of the activated carbon is less than 3%; (6) The powder conductivity of the activated carbon is 10 - 40 S / cm; (7) The median particle size of the activated carbon is 3-8 um.

4. A method for preparing activated carbon according to any one of claims 1 to 3, characterized in that: include: mixing the carbonized material with the activator to obtain a mixed material; The mixed material is first activated in an inert gas and CO2 gas to obtain a granulated material; The granulated material is subjected to a second activation in water vapor to obtain an activated material, wherein the temperature of the second activation is 700-800°C; The activated material is purified, crushed and sintered to obtain the activated carbon.

5. The method for preparing activated carbon according to claim 4, characterized in that: At least one of the following conditions is met: A. The carbonized material includes at least one of petroleum coke, coal, coconut shell, apricot shell, walnut shell, bamboo, phenolic resin, urea-formaldehyde resin, polyvinyl chloride, and asphalt; B. the activator is at least one of sodium hydroxide, potassium hydroxide and calcium hydroxide; C. The mixing method is mechanical mixing; D. The mass ratio of the carbonized material to the activator is 1:(1.2-2.5).

6. The method for preparing activated carbon according to claim 4, characterized in that: At least one of the following conditions is met: E. The flow rate of the inert gas is 200-1000 sccm; F. The flow rate of the CO2 gas is 5-200 sccm; G. the temperature of the first activation is 350-650°C; H. The first activation insulation time is 10-60 min.

7. The method for preparing activated carbon according to claim 4, characterized in that: At least one of the following conditions is met: a. The flow rate of the water vapor is 0.1 L / min-0.3 L / min; b. The second activation holding time is 1-3h.

8. The method for preparing activated carbon according to claim 4, characterized in that: The purification includes water washing and acid washing; the preparation method satisfies at least one of the following conditions: d. The mass ratio of the water to the carbonized material is 1-100:1; e. The mass concentration of the acid is 10-30%; f. The acid comprises at least one of sulfuric acid, hydrochloric acid, hydrofluoric acid and nitric acid.

9. A capacitor, characterized in that: The activated carbon according to any one of claims 1 to 3 is used as an electrode.

Citation Information

Patent Citations

  • Activated carbon and process of making the same

    CN101218174A

  • Activated carbon for supercapacitor and preparation method of activated carbon

    CN107892298A